Development of Spinning Wheel Learning Media with QR Code Material my Dear Earth, my Poor Earth to Improve Science Learning Outcomes of Grade V Students - Maharani Ardhita Putri; Fitria Dwi Prasetyaningtyas (Postgraduate, University of Mataram, 2025)
This development research aims to develop media design and test the feasibility of the rotating wheel learning media with QR Code material on my dear earth, my poor earth for the subject of science. The rotating wheel media with QR Code is one example of interactive media and is able to stimulate active participation of students. QR Code that can quickly and easily access teaching materials and instructions for using the media. This type of research is Research and Development (R&D) with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The subjects in this study were 25 students of grade V SDN Pati Lor 05, Pati Regency. The data collection techniques used were media expert validation questionnaires, material expert validation questionnaires, teacher response questionnaires, and student response questionnaires. The results of this study indicate that the Development of Spinning Wheel Learning Media with QR Code is feasible to use, based on the assessment of media experts and material experts with a percentage of material feasibility of 84% and a percentage of media feasibility of 94% with the category